Analysis of Determining Factors of Student Success in the Indonesian International Student Mobility Awards (Iisma) Program Within the MBKM Policy at the State Polytechnic of Manado - Pantow, Vincentius; Mandang, Selvie; Longdong, Wingston (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) policy has become crucial in transforming higher education in Indonesia. One of the programs adopted within the MBKM framework is the Indonesian International Student Mobility Award (IISMA), aimed at enhancing international student mobility. This study analyzes the factors determining student success in the IISMA program at the State Polytechnic of Manado. The research methodology used is qualitative, with data collection techniques in the form of observation, interviews, and literature review. Meanwhile, the data analysis technique uses the Miles and Huberman method. The tentative observation shows that the critical determinants of success are highlighted factors such as student motivation, English language proficiency, academic and administrative support, and international experience. The implications of this research underscore the importance of considering these factors in designing policies and supporting programs for students interested in international programs at universities. This study is expected to provide valuable insights for developing policies and implementing MBKM programs at the institutional level, particularly at the State Polytechnic of Manado and other educational institutions in general.